THE ROLE OF ARTIFICIAL INTELLIGENCE AND DIGITAL TECHNOLOGIES IN THE ACQUISITION OF MEDICAL TERMINOLOGY IN LATIN (Uzbekistan Open Conference, 2026)
This article examines the role of artificial intelligence and digital technologies in the acquisition of Latin medical terminology by medical university students. Adaptive learning platforms, neural networks, mobile applications and virtual reality are considered as tools for improving memorization of terms. The necessity of integrating digital methods into the traditional medical education system for building professional competence of future physicians is substantiated.